jQC-PET, an ImageJ macro to analyse the quality control of a PET/CT (Revista de Física Médica, 2016)
An ImageJ macro has been developed to facilitate the analysis of three PET/CT quality control procedures included in the documents from the National Electrical Manufacturers Association (NU2-2007) and the International Atomic Energy Agency (Pub-1393): image quality, uniformity and spatial resolution. In them, the generation of the regions of interest and the analysis are automatized. The results obtained with the software have been compared with those of the commercial software and the literature. The use of jQC-PET allows a standard analysis and the independence of the commercial software.